PHILOSOPHICAL AND PSYCHOLOGICAL DIMENSIONS OF SOCIAL EXPECTATIONS OF PERSONALITY - V. V. Khmil; I. S. Popovych (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. To analyse the philosophical and psychological contexts of social expectations of personality, to form general scientific provisions, to reveal the properties, patterns of formation, development and functioning of social expectations as a process, result of reflection and construction of social reality. Theoretical basis of the study is based on the phenomenology of E. Husserl, the social constructivism philosophy of L. S. Vygotskiy, P. Berger, T. Luckmann, K. J. Gergen, ideas of constructive alternativeism of G. Kelly, psychology of social expectations of a personality as the unity of the mental process, mental state and properties of expectations. Originality. Social expectations of personality are considered as philosophical and psychological dimensions of the study, presented by analysing expectations in social constructivism, externalizing, building a model of the expected future. The authors clarified some theoretical and methodological aspects of the study of patterns of social expectations in the reflection and construction of social reality. The role of social institutions in the formation of expectations is outlined. The poly-aspect of the investigated problems is shown. It is substantiated that formation, realization of social expectations in organization of interaction of personality and social environment is possible in the presence of subject, object and content of activity. Conclusions. Social expectations influence social behaviour and determine the behaviour of an individual, small contact group, community, or large mass of people. Social expectations are able to set specific requirements, norms, sanctions, ideals that participants of the process must follow or must not violate. The philosophical dimension of the study integrates the ontological, epistemological, axiological preconditions for the formation and realization of the social ideal, represented by the study of the expected future in the forms of utopia, eschatology and thanatology. Psychological dimension of the study has a sufficiently developed content orientation from the psychological content parameters of social expectations to the role of expectations in social institutions and various spheres of human life. Systematic, actionable, self-regulatory, and subjective approaches have constituted a verified system of interpreting the social expectations of personality as a process, a result of the reflection and construction of social reality. The topic of social expectations of personality is far from being completed, in our opinion it is promising to create a deeper philosophical concept of social expectations of the personality. The specific topics are of particular relevance in the context of socio-political uncertainty, domination of the mass consciousness, loss of national and cultural identity.